2020
DOI: 10.1186/s13550-020-0595-5
|View full text |Cite
|
Sign up to set email alerts
|

Pre-test 68Ga-PSMA-ligand PET/CT positivity in early biochemical recurrent prostate cancer after radical prostatectomy—validation of a prediction model

Abstract: Objectives: The aim of this study was the validation of a recently established comprehensive and compact prediction model for 68 Ga-PSMA-11-ligand positron-emission tomography (PET) positivity with an independent subsequent patient series. Methods: A total of 292 consecutive patients with early biochemical recurrence after radical prostatectomy and PSA values between 0.2 and 1 ng/ml who underwent 68 Ga-PSMA-11-ligand PET/computed tomography (CT) between January 2016 and June 2017 were retrospectively included.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
2
1
0
Order By: Relevance
“…Several teams recently elaborated nomograms, which do not incorporate the results of FCH PET/CT, in contrast with ours. Rauscher et al [29] proposed two predictive models; a validation study [30] showed similar predictive values as ours, and the authors conclude that the prediction models should rather be understood as a tool for a positive decision towards a PSMA-ligand PET/CT examination. Another model integrating more clinical information has recently been proposed by Ceci et al [31] achieving a PPV of 81%, similar to ours, but a greater NPV of 76%.…”
Section: Relation With Fch Pet/ctsupporting
confidence: 69%
“…Several teams recently elaborated nomograms, which do not incorporate the results of FCH PET/CT, in contrast with ours. Rauscher et al [29] proposed two predictive models; a validation study [30] showed similar predictive values as ours, and the authors conclude that the prediction models should rather be understood as a tool for a positive decision towards a PSMA-ligand PET/CT examination. Another model integrating more clinical information has recently been proposed by Ceci et al [31] achieving a PPV of 81%, similar to ours, but a greater NPV of 76%.…”
Section: Relation With Fch Pet/ctsupporting
confidence: 69%
“…Thus, currently 68 Ga‐PSMA PET/CT underestimates the extent of the disease, and patients with lymph node‐positive PCa often harbour microscopic metastatic PCa. Our detection rates, stratified by the different PSA values, are in accordance with earlier publications [12]. In our analysis, we did not focus on other predictors of positive 68 Ga‐PSMA PET/CT, such as grade group, and the study only included patients with high‐risk PCa, and the correlation between predictors and the chance of having a positive PSMA PET/CT has already been described and externally validated [12].…”
Section: Discussionsupporting
confidence: 53%
“…The same group proposed in-house validation of the model in an external cohort [26], showing high concordance of the calculated probabilities and PSMA-PET findings, while further external validation [27] did not confirm these results, showing an overestimation throughout the range of predicted positive PSMA-PET probabilities. However, this model cannot be fully compared with our nomogram, considering the strict patient selection and the lack of clinical data (eg, PSAdt and clinical setting).…”
Section: Discussionmentioning
confidence: 97%